Galla rhois water extract inhibits enzymatic browning in apple juice partly by binding to and inactivating polyphenol oxidase - Lee, Min-Kyeong; Hwang, Youn-Hwan; Ryu, Heeyeon; Lee, Ami; Jeong, Hyeon Hak; Baek, Jiwon; Kim, Myeong-Jin; Lee, Ji Yun; Van, Ji Yun; Liu, Yunshan; Choi, Chun Whan; Kim, Min Soo; et al. (Elsevier BV, 2022)
Although Galla rhois has been used as a traditional medicine in Asian countries, there was no application of it in anti-browning food additives. Here, we tested whether Galla rhois inhibits apple juice browning. Apple juice browning was blocked at 250-1000 mu g/ml of Galla rhois for 16 days but the effect of vitamin C did not last until a day. In vitro assays showed that the antioxidant capacity of Galla rhois was stronger than that of vitamin C. Further analysis by UPLC-MS/MS identified 17 phytochemicals containing gallotannin derivatives. Docking simulation and polyphenol oxidase activity assay indicate that the mechanisms underlying Galla rhois-mediated inhibition of the enzymatic browning include but are not limited to the combined effects of multiple compounds including galloylglucose-and gallate-derivates. Although marketability and long-term toxicity of Galla rhois should be tested, it may be applied as a food additive to elevate food quality.